Culprit site extracellular DNA and microvascular obstruction in ST-elevation myocardial infarction. Issue 8 (26th June 2021) - Mangold, Andreas; Ondracek, Anna S; Hofbauer, Thomas M; Scherz, Thomas; Artner, Tyler; Panagiotides, Noel; Beitzke, Dietrich; Ruzicka, Gerhard; Nistler, Sonja; Wohlschläger-Krenn, Evelyne; Winker, Robert; Quehenberger, Peter; et al.
Abstract: Aims: Extracellular chromatin and deoxyribonuclease (DNase) have been identified as important players of thrombosis, inflammation, and homeostasis in a murine model. We previously demonstrated that activated neutrophils release neutrophil extracellular traps (NETs) at the culprit site in ST-elevation myocardial infarction (STEMI), which significantly contribute to extracellular chromatin burden, and are associated with larger infarcts. To understand the correlation between neutrophil activation, extracellular chromatin, and infarct size (IS), we investigated these parameters in a porcine myocardial infarction model, and at different time points and sites in a prospective STEMI trial with cardiac magnetic resonance (CMR) endpoints. Methods and results: In a prospective STEMI trial (NCT01777750), 101 STEMI patients were included and blood samples were obtained from first medical contact until 6 months after primary percutaneous coronary intervention (pPCI) including direct sampling from the culprit site. CMR was performed 4 ± 2 days and 6 months after pPCI. Neutrophil counts, markers of extracellular chromatin, and inflammation were measured. Double-stranded deoxyribonucleic acid (dsDNA), citrullinated histone 3, nucleosomes, myeloperoxidase, neutrophil elastase, and interleukin (IL)-6 were significantly increased, while DNase activity was significantly decreased at the culprit site in STEMI patients. High neutrophil counts and dsDNA levels at the culprit site correlated with high microvascular obstruction (MVO) and low ejection fraction (EF). High DNase activity at the culprit site correlated with low MVO and high EF. In correspondence, dsDNA correlated with IS in the porcine myocardial infarction model. In porcine infarcts, neutrophils and extracellular chromatin were detected in congested small arteries corresponding with MVO. Markers of neutrophil activation, extracellular chromatin, DNase activity and CMR measurements correlated with markers of systemic inflammation C-reactive protein and IL-6 in patients. Conclusions: NETs and extracellular chromatin are important determinants of MVO in STEMI. Rapid degradation of extracellular chromatin by DNases appears to be crucial for microvascular patency and outcome. Graphical Abstract: